2022
DOI: 10.1002/cb.2074
|View full text |Cite
|
Sign up to set email alerts
|

The development of reputational capital – How social media influencers differ from traditional celebrities

Abstract: Social media influencers (SMI) have grown in importance as a promotional channel.However, little is known about how they build reputational capital and thus endorsement effectiveness, particularly compared to traditional celebrity endorsers. From a consumers' perspective, this research investigates both types of endorsers in different stages of the Celebrity Capital Life Cycle (CCLC). Across three studies, we find that parasocial relationships and interactions with consumers are paramount for SMIs reputational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The size of the audience is a reliable sign of how much attention journalists receive. It can represent both individual capital, such as social media followers for noninstitutionally embedded influencers (Hess et al, 2022), and organizational capital, which spills over onto embedded individuals. The size of an individual journalist's audience is very dynamic and difficult to determine, especially for printed newspapers.…”
Section: Size Of Audiencementioning
confidence: 99%
“…The size of the audience is a reliable sign of how much attention journalists receive. It can represent both individual capital, such as social media followers for noninstitutionally embedded influencers (Hess et al, 2022), and organizational capital, which spills over onto embedded individuals. The size of an individual journalist's audience is very dynamic and difficult to determine, especially for printed newspapers.…”
Section: Size Of Audiencementioning
confidence: 99%
“…However, if consumers are skeptical of online information, then this will significantly reduce the overall effectiveness of online influencers’ endorsements (Jamil and Qayyum, 2022). Hess et al (2022) concluded that the type of endorser does not have a significant effect on word-of-mouth but that consumers prefer to recommend brands endorsed by online influencers with whom they have highly parasocial interactions, while this type of relationship is not relevant to traditional celebrities. Despite growing evidence indicating that online influencers occupy a unique position in consumers’ minds that differs from that of traditional celebrities, research has not provided a plausible or general explanation for this distinction or how it impacts the effectiveness of endorsements (Gräve and Bartsch, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike conventional endorsers, social media influencers co-create brand images with their followers on social media platforms (Bu et al, 2022;Halder et al, 2021). Additionally, followers on social media continuously engage in the influencers' lives, offering direct interaction opportunities and fostering a sense of closeness compared to celebrities (Hess et al, 2022;Lee et al, 2021;Torres et al, 2019).…”
Section: Social Media and Virtual Influencersmentioning
confidence: 99%